1998
DOI: 10.1515/zna-1998-0518
|View full text |Cite
|
Sign up to set email alerts
|

Three-body Effects in Calcium(II)-ammonia Solutions: Molecular Dynamics Simulations

Abstract: Molecular dynamics simulations have been performed with and without three-body corrections at an average temperature of 240 K using a flexible ammonia model. The system consists of one calcium ion and 215 ammonia molecules. The calcium(II)-ammonia interactions were newly developed, based on ab initio calculations with a basis set of double zeta quality. The role of three-body interactions on the structural and dynamical properties of the solution has been investigated. The presence of three-body corrections le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…48 The situation is not different for Mg 2+ , where only an early proton magnetic resonance study is reported in which CN = 6 was found. 49 The ammonia solvation of Ca 2+ has been studied theoretically; [43][44][45][46][47]50 however, basic information about the structure of the dominant solvation motif is still unclear. Sidhisoradej et al performed molecular dynamics (MD) simulations of infinitely dilute Ca 2+ −ammonia solutions including two-and three-body effects.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…48 The situation is not different for Mg 2+ , where only an early proton magnetic resonance study is reported in which CN = 6 was found. 49 The ammonia solvation of Ca 2+ has been studied theoretically; [43][44][45][46][47]50 however, basic information about the structure of the dominant solvation motif is still unclear. Sidhisoradej et al performed molecular dynamics (MD) simulations of infinitely dilute Ca 2+ −ammonia solutions including two-and three-body effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Sidhisoradej et al performed molecular dynamics (MD) simulations of infinitely dilute Ca 2+ −ammonia solutions including two-and three-body effects. 47 They found that the inclusion of three-body corrections produces CN = 8 with an average Ca−N distance of 2.86 Å, while taking into account that only two-body interactions produce CN = 9 at a distance of 2.53 Å. Floris et al developed an effective ab initio pair potential 45 and used it to search for local minimum structures of [Ca(NH 3 ) n ] 2+ with n ≤ 10; they employed it later to conduct molecular dynamics simulations of aqueous solutions containing ammonia. 50 Kerdcharoen et al performed quantum mechanics/molecular mechanics (QM/MM) MD simulations (under the ONIOM framework) 43 and found that Ca 2+ is sixcoordinate in a near-octahedral fashion with a mean Ca−N distance of 2.53 Å.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the statistical simulations performed so far and dealing with the solvation phenomenon of this cation are specifically devoted to the study of the hydration 4 -18 of calcium ion, and, marginally, solvation properties including other solvents have been considered at a quantum chemical level. [19][20][21][22][23] To our best knowledge, only the work done by Sidhisoradej et al 24 studies the solvation of Ca 2ϩ in liquid ammonia by means of molecular dynamics ͑MD͒ simulations using a potential function which explicitly considers threebody effects in the ion-solvent potential. However, studies including more than one solvent have not been considered so far, despite being the most common situation in the biological media.…”
Section: Introductionmentioning
confidence: 99%
“…16 For the coordination numbers of Ca 2þ in liquid ammonia, early MC simulations reported 9 and 8.2, as observed from pair and pair plus threebody correction simulations, respectively. 61 No structural properties for this ion in aqueous ammonia solution have been reported so far and therefore they are the main subject of interest in this paper.…”
Section: Introductionmentioning
confidence: 99%